72.4k views
4 votes
The difference between the two roots of the equation 3x^2+10x+c=0 is 4 2/3 . Find the solutions for the equation.

1 Answer

1 vote

Answer:

Given the equation:
3x^2+10x+c =0

A quadratic equation is in the form:
ax^2+bx+c = 0 where a, b ,c are the coefficient and a≠0 then the solution is given by :


x_(1,2) = (-b\pm √(b^2-4ac))/(2a) ......[1]

On comparing with given equation we get;

a =3 , b = 10

then, substitute these in equation [1] to solve for c;


x_(1,2) = (-10\pm √(10^2-4\cdot 3 \cdot c))/(2 \cdot 3)

Simplify:


x_(1,2) = (-10\pm √(100- 12c))/(6)

Also, it is given that the difference of two roots of the given equation is
4(2)/(3) = (14)/(3)

i.e,


x_1 -x_2 = (14)/(3)

Here,


x_1 = (-10 + √(100- 12c))/(6) , ......[2]


x_2= (-10 - √(100- 12c))/(6) .....[3]

then;


(-10 + √(100- 12c))/(6) - ((-10 + √(100- 12c))/(6)) = (14)/(3)

simplify:


(2 √(100- 12c) )/(6) = (14)/(3)

or


√(100- 12c) = 14

Squaring both sides we get;


100-12c = 196

Subtract 100 from both sides, we get


100-12c -100= 196-100

Simplify:

-12c = -96

Divide both sides by -12 we get;

c = 8

Substitute the value of c in equation [2] and [3]; to solve
x_1 , x_2


x_1 = (-10 + √(100- 12\cdot 8))/(6)

or


x_1 = (-10 + √(100- 96))/(6) or


x_1 = (-10 + √(4))/(6)

Simplify:


x_1 = (-4)/(3)

Now, to solve for
x_2 ;


x_2 = (-10 - √(100- 12\cdot 8))/(6)

or


x_2 = (-10 - √(100- 96))/(6) or


x_2 = (-10 - √(4))/(6)

Simplify:


x_2 = -2

therefore, the solution for the given equation is:
-(4)/(3) and -2.


User Mudasser Hassan
by
5.3k points